Odpowiedzi

2009-12-04T15:36:51+01:00
1.
a)(a+7)=a²+14a+49
b)(1,2+b)²=1,44+2,4b+b²
c)(c+1 2/3)²=c²+3 1/3c+2 7/9
d)(√5-d)²=5-2√5d+d²
e)(3k+ 2/5)²=9k²+1 1/5+4/25
f)(5m+6n)²=25m²+60mn+36n²

2.
a)(z-9)²=z²-18z+81
b)(0,7-w)²=0,49-1,4w+w²
c)(u-2 1/3)²=u²-4 2/3u+ 5 4/9
d)(√3-v)²=3-v√3+v²
e)(3y-3/4)²=9y²-4,5y+9/16
f)(1,1-0,3x)²=1,21-0,66x+0,09x²























2009-12-04T18:25:02+01:00
1.
a)(a + 7) = a² + 14a + 49
b) (1,2 + b)² = 1,44 + 2,4b + b²
c) (c + 1 2/3)² = (c + 5/3)² = c² + 3 1/3c + 25/9 = c² + 3 1/3c + 2 7/9
d) (√5 - d)² = 5 - 2√5d + d²
e) (3k+ 2/5)² = 9k² +2 2/5 + 4/25
f) (5m + 6n)² = 25m²+ 60mn + 36n²

2.
a) (z - 9)² = z² - 18z + 81
b) (0,7 - w)² = 0,49 - 1,4w + w²
c) (u - 2 1/3)² = (u - 7/3)² = u² - 4 2/3u + 49/9 = u² - 4 2/3u + 5 4/9
d) (√3 - v)² = 3 - 2v√3 + v²
e) (3y - 3/4)² = 9y² - 4,5y + 9/16
f) (1,1 - 0,3x)² = 1,21 - 0,66x + 0,09x²